أنموذج إنسان الحداثة في المقاربة الرؤيوية إلى العالم - نصر الدين بن سراي (مجلة الآداب و العلوم الإجتماعية, 2015)
In the World's Intellectual fact, today there are many and varied visions, which tries to present itself as a vision bringing the salvation of humanity with concepts and projects. among them, the one presented by modernity, which took the ethereal character echoing the intellectual world, considered as a world view that tried to provide a vision to build a modern man according to his worldview, which confirmed the primacy of the spirit and respect for the human being, through the mental tendency, inherited to physical science, to approximate the notion of humanity through these two narrow aims, later excluded the spiritual after the man has become the reference of himself, and in this study we try to question the visionary character of modernity on the concept of modern humanity, using that vision to the world as a procedural tool for this questionning, to investigate which is invisible in the conceptual and intellectual worlds of modernity.